Medical Applications of Tissue-Equivalent, Organic-Based Flexible Direct X-Ray Detectors - Basiricò, Laura; Ciavatti, Andrea; Fratelli, Ilaria; Dreossi, Diego; Tromba, Giuliana; Lai, Stefano; Cosseddu, Piero; Bonfiglio, Annalisa; Mariotti, Francesco; Dalla Val, Carlo; Bellucci, Valerio; Anthony, John E.; et al. (Frontiers in Physics, 2020)
The aim of this study is to assess direct X-ray detectors based on organic thin films, fabricated onto flexible plastic substrates and operating at ultra-low bias (<1 V), for different medical applications. With this purpose, flexible fully organic pixelated X-ray detectors have been tested at the imaging beamline SYRMEP (SYnchrotron Radiation for MEdical Physics) at the Italian synchrotron Elettra, Trieste. The detectors’ performance has been assessed for potential employment both as reliable wearable personal dosimeters for patients and as flexible X-ray medical imaging systems. A spatial resolution of 1.4 lp mm-1 with a contrast of 0.37 has been evaluated. Finally, we validate the detector using X-ray doses and energies typically employed for actual medical radiography, and using X-ray beam pulses provided by a commercial dental radiography system, recording a sensitivity of 1.6×105 µC Gy-1 cm-3 with a linear response with increasing of the dose rates and a reliable signal to 100 ms X-rays pulses.